Global Response towards the Transnationalism of Illegal Rhinoceros Commodity Hunting and Trading in South Africa - Numadi, Katong Ragawi; Ma'rifat, Filasafia Marsya (Global Strategis, 2023)
Globalization, which coincides with the formation of a global economic network, has provided convenience in various aspects as well as created new threats, one of them is illegal poaching and illegal trade in wildlife commodities. This is illustrated in this paper through the integration of Africa into the dynamics of the global economy which also has a negative impact in the form of increasing cases of illegal poaching and trade in wildlife commodities, especially African rhino species. The results of this qualitative research found that the issue of poaching wild rhinos in the African region experienced a drastic increase in the early 2010s and reached its peak in 2016 with South Africa as the hotspot as well as the starting point of the supply chain on this issue. Even though the South African government has ratified the Convention on International Trades on Endangered Species of Wild Flora and Fauna (CITES) and made various prevention efforts, the South African government is still experiencing bureaucratic limitations and conflicts of interest in dealing with this issue. As a result, the "transnational” term of illegal wildlife hunting and trade operations also requires other collaborative steps involving various international state organizations (IGOs) and non-state (INGOs) working in the same field. Keywords: Rhinoceros, Rhino Horn, South Africa, Poaching, Illicit Trade   Globalisasi yang bersamaan dengan terbentuknya jaringan perekonomian global pada faktanya telah memberikan kemudahan di berbagai aspek sekaligus memunculkan berbagai ancaman baru, salah satunya adalah perburuan dan perdagangan komoditas margasatwa ilegal. Hal tersebut diilustrasikan dalam tulisan ini melalui integrasi Afrika ke dalam dinamika ekonomi global yang tidak hanya berdampak positif, tetapi juga memunculkan dampak negatif berupa meningkatnya kasus perburuan dan perdagangan komoditas margasatwa ilegal, khususnya spesies badak Afrika. Hasil penelitian kualitatif ini menemukan bahwa isu perburuan badak liar di wilayah Afrika mengalami peningkatan drastis di awal dekade 2010-an dan mencapai puncaknya pada tahun 2016 dengan Afrika Selatan sebagai hotspot sekaligus titik awal rantai suplai dalam isu tersebut. Kendati pemerintah Afrika Selatan telah meratifikasi Convention on International Trades on Endangered Species of Wild Flora and Fauna (CITES) dan melakukan berbagai upaya pencegahan, pemerintah Afrika Selatan nyatanya masih mengalami keterbatasan birokrasi dan konflik kepentingan dalam mengatasi isu tersebut. Alhasil, sifat transnasional dalam operasi perburuan dan perdagangan satwa ilegal juga menuntut adanya langkah kolaboratif lain yang melibatkan berbagai organisasi internasional negara (IGOs) dan non-negara (INGOs) yang bergerak di bidang yang sama. Kata-kata Kunci: Badak, Cula Badak, Afrika Selatan, Perburuan, dan Perdagangan Ilegal